The numbers given in the problem above are part of an arithmetic sequence with first and sixth terms equal to -21 and -36, respectively. Firstly, calculate for the common difference (d).
d = (-36 - -21) / (6 - 1) = -3
The arithmetic mean is calculated by adding -3 to the term prior to it.
a2 = -21 + -3 = -24 a3 = -24 + -3 = -27
a4 = -27 + -3 = -30 a5 = -30 + -3 = -33
Thus the four arithmetic means are -24, -27, -30, and -33.
9 x 8 = 72
9 + 9 +9 + 9 + 9 +9 + 9 + 9 = 72
858.666666666666666666666666666666666666666666666666666666666
Answer:
Step-by-step explanation:
![(\sqrt{2}+3)^2=(\sqrt{2})^2 + 6\sqrt{2}+9 = 6\sqrt{2} +9+2=6\sqrt{2}+11](https://tex.z-dn.net/?f=%28%5Csqrt%7B2%7D%2B3%29%5E2%3D%28%5Csqrt%7B2%7D%29%5E2%20%2B%206%5Csqrt%7B2%7D%2B9%20%3D%206%5Csqrt%7B2%7D%20%2B9%2B2%3D6%5Csqrt%7B2%7D%2B11)
hope this helps